Ultraviolet diversity of Type Ia Supernovae. Issue 2 (16th June 2016) - Foley, Ryan J.; Pan, Yen-Chen; Brown, P.; Filippenko, A. V.; Fox, O. D.; Hillebrandt, W.; Kirshner, R. P.; Marion, G. H.; Milne, P. A.; Parrent, J. T.; Pignata, G.; Stritzinger, M. D.
Abstract: Ultraviolet (UV) observations of Type Ia supernovae (SNe Ia) probe the outermost layers of the explosion, and UV spectra of SNe Ia are expected to be extremely sensitive to differences in progenitor composition and the details of the explosion. Here, we present the first study of a sample of high signal-to-noise ratio SN Ia spectra that extend blueward of 2900 Å. We focus on spectra taken within 5 d of maximum brightness. Our sample of 10 SNe Ia spans, the majority of the parameter space of SN Ia optical diversity. We find that SNe Ia have significantly more diversity in the UV than in the optical, with the spectral variance continuing to increase with decreasing wavelengths until at least 1800 Å (the limit of our data). The majority of the UV variance correlates with optical light-curve shape, while there are no obvious and unique correlations between spectral shape and either ejecta velocity or host-galaxy morphology. Using light-curve shape as the primary variable, we create a UV spectral model for SNe Ia at peak brightness. With the model, we can examine how individual SNe vary relative to expectations based on only their light-curve shape. Doing this, we confirm an excess of flux for SN 2011fe at short wavelengths, consistent with its progenitor having a subsolar metallicity. While most other SNe Ia do not show large deviations from the model, ASASSN-14lp has a deficit of flux at short wavelengths, suggesting that its progenitor was relatively metal rich.